THE CORRELATION AMONG MOTIVATION, ANXIETY, AND SPEAKING ABILITYON 3 DIPLOMASTUDENTS IN PALEMBANG - Arief Pamuji (Language and Education Journal, 2019)
The objective of this researchwas to find out whether or not therewasa correlation among motivation, anxiety, and speaking ability. The sample of this research was taken by using total sampling with a total of 105students of STIK Bina Husada, STIKES Pembina,and PolytechnicAnika Palembang in the academic year of 2018/2019. The data were obtained by using questionnairesand speaking test. To verify the hypotheses, the primary data were analyzed by using correlation and regression analyses by means of SPSS version 21.00 computer program. Based on the data analysis, the correlation coefficient (rxy)was 0.959at the significance level of p< 0.05 in two-tailed. Since the value of robtained was higher than the critical value of rtable (0.959>0.1918), the null hypothesis (Ho) was rejected and consequently, the research hypothesis (Ha) was accepted. This showeda significant correlation among motivation, anxiety and speaking ability on diploma students in Palembang. ThenR2 (the coefficient determiner) was 0.92, it meant that motivationinfluenced the students’ anxiety and speaking ability was 92%. In other words, there was a significant influence of motivationon the students’ anxiety and speaking ability